THE CHANGES OF FISH FARMER’S LIVELIHOOD IN SILALAHI III VILLAGE SILAHISABUNGAN SUBDISTRICT DAIRI REGENCY NORTH SUMATERA PROVINCE - Jenita Rajagukguk; Firman Nugroho; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTCommunity of Silalahi III Village mostly looked at fish farmers using floating net cages in Lake Toba waters, based on Presidential Decree No. 81 of 2014 in terms of cultivation area control, conducted fish folk. This research discusses the characteristics of fish farmers and the change of livelihood of fish farmers in Silalahi III Village, Silahisabungan Sub-district, Dairi Regency. The research method used survey method with data retrieval technique that is in-depth interview, field documentation and questionnaire analyzed descriptively qualitative. The results showed the characteristics of fish farmers in the village of Silalahi III age group is very productive 15-45 years old; high school / senior high school; the number of family dependents is less than 4 people; and cultivation experience less than 3 years. The application of Pepres 81/2014 resulted in a change in the livelihood of fish cultivators, namely income decreased 14.81%; 37% employment diversification and total employment decreased by 3.70%; food consumption decreased 22.23%; social condition is cooperation relationship not continue and respondent have other job opportunity; human resources do not follow training continuously; sanitation cleanliness (clean water source 7.4% switched to lake water, all respondents had their own toilet and 51.85% and 48.14% semipermanent house housing with cement and board floor). Based on these changes, fish farmers in Silalahi III Village can still meet their daily needs. Key words : Characteristics, Livelihood Changes, Fish Farmer, Initial and Final Condition